EVALUASI KOMPOSISI BOTANI DAN NILAI NUTRIEN PADA RUMPUT DI RAWA KECAMATAN MENGGALA KABUPATEN TULANG BAWANG - Ridho Akbar; Liman Liman; Agung Kusuma Wijaya (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
This research aimed to determine the botanical composition and nutrient value of grass in swamp of Menggala Sub-District Tulang Bawang Regency Lampung Province in August--October 2017. This research used survey method with purposive sampling. The data obtained from this study consisted of primary and secondary datas. The result showed that the botanical composition contained in the swamp of Hymenachne amplexicaulis 59,93%; Cynodon dactylon L. Pars 18,54%; Fimbristylis vahlii 7,54%; Brachiaria plantaginea 7,39% and Isachne indica Nees 6,60%. The average nutrient of grass contained in swamp of Menggala Sub-District were dry material 19.72%; crude fiber 28,90%; crude protein 5.72%; crude fat 4.51%; ash 14.05%; and NFE 42.16%. Keywords:  Botanical Composition, Menggala Sub-District, Nutrient Value, Swamp